Acute Mastoiditis in a Newborn with Aural Atresia - K. Parpounas; K. Bouka; J. Athanasopoulos; M. Lamprou; G. Helmis; I. M. Vlastos (Case Reports in Otolaryngology)
Acute mastoiditis in the newborn is a very rare disease. Herein we report a case of a 28-day-old child with right aural atresia and ipsilateral mastoiditis requiring mastoidectomy. To our knowledge, this is the youngest case reported in the literature. Issues on diagnosis and management of mastoiditis in cases of aural atresia are further discussed. Based on our experience and on previous reported cases we conclude that mastoiditis is difficult to diagnose in a child with aural atresia. Moreover, mastoidectomy may be necessary, although identification of the facial nerve and consequent treatment of the atresia are usually too difficult to perform simultaneously.